Comparison between chromatofocusing and icIEF charge variant profiles of unconjugated monoclonal antibodies and their drug conjugates - ثلاج ناصر; آيات عبود (Latakia University Journal -Medical Sciences Series, 2023)
Assessing charge variant profiles is one of the tools used to insure the quality of monoclonal antibody (mAb) and their drug conjugates (ADC). In this study, the charge variant profiles obtained by weak anion exchange chromatofocusing and icIEF methods for two unconjugated antibodies (mAb-1 and mAb-2) and their maytansine conjugates were compared. Significant differences were observed between chromatofocusing and icIEF profiles for studied mAbs and ADCs. The charge chromatofocusing profile of mAb-1 showed two main peaks (pI values 8.1 and 8.2) and one minor peak (pI value: 7.9). While its icIEF profile demonstrated two main peaks (pI values: 7.9 and 8.1) and two minor peaks (pI values: 7.7 and 8.2). mAb-2 was more basic and homogenous with one major peak (pI value 8.7) using chromatofocusing method and two peaks (pI values: 8.9 and 9.0) using icIEF method. The studied conjugated antibodies had more heterogeneous and basic charge variant profile than their unconjugated mAbs. The charge variant profile for studied ADCs varied between chromatofocusing and icIEF methods. icIEF method was capable to separate the charge variants of mAbs and their conjugates with good resolution in comparison to the chromatofocusing method and therefore was more powerful to characterize and to determine the presence of any changes in charge variant profile of these products.